Abordaje retrosigmoideo para clipaje de aneurisma distal de la AICA - Espinosa Mora, José Alfredo; Becerra Escobedo, Guillermo; Barrios Garcia, Sergio; Ramirez Aguilar, Ricardo; Ordoñez Granja, Jaime; Castillo Rangel, Carlos (Revista Argentina de Neurocirugía, 2020)
Background: Cerebral aneurysms of the posterior circulation, representing only 8 to 10% of the total cerebral aneurysms, but the aneurysms of the anteroinferior cerebellar artery (AICA) are very rare, so there is no management algorithm for these lesions, anatomical knowledge of vascular and skull base are known for the treatment of these lesions, in relation of the surgical approach, we can identify, the far lateral, retrosigmoid, orbitozigmatic or presigmoid approaches, which depends on the size and location of aneurysm, either distal or proximal. We present this case, which we treated through a conventional retrosigmoid approach, which offers us a sufficient surgical corridor, without the need for a broader approach, in this case it was a distal AICA aneurysm, located in the meatal segment, which was found in the middle neurovascular complex of the pontocerebellar angle, very close to the cranial nerves V, VII and VIII.Objective: Demonstrate that distal aneurysms of AICA can be managed using a successful conventional retrosigmoid approach.Results: The clipping of the aneurysm was achieved satisfactorily, with a good clinical result of the patient, who was discharged at 4 days without neurological deficit.Conclusion: The retrosigmoid approach is a therapeutic option for the management of aneurysms located in the pontocerebellar angle, specifically of the distal AICA and can also be used even for distal aneurysms of the PICA.
Keywords: Anteroinferior Cerebellar Artery Aneurysm; Retrosigmoid; AICA Aneurysm